Habitat heterogeneity favors asexual reproduction in natural populations of grassthrips. (13th July 2016) - Lavanchy, Guillaume; Strehler, Marie; Llanos Roman, Maria Noemi; Lessard‐Therrien, Malie; Humbert, Jean‐Yves; Dumas, Zoé; Jalvingh, Kirsten; Ghali, Karim; Fontcuberta García‐Cuenca, Amaranta; Zijlstra, Bart; Arlettaz, Raphaël; Schwander, Tanja
Abstract : Explaining the overwhelming success of sex among eukaryotes is difficult given the obvious costs of sex relative to asexuality. Different studies have shown that sex can provide benefits in spatially heterogeneous environments under specific conditions, but whether spatial heterogeneity commonly contributes to the maintenance of sex in natural populations remains unknown. We experimentally manipulated habitat heterogeneity for sexual and asexual thrips lineages in natural populations and under seminatural mesocosm conditions by varying the number of hostplants available to these herbivorous insects. Asexual lineages rapidly replaced the sexual ones, independently of the level of habitat heterogeneity in mesocosms. In natural populations, the success of sexual thrips decreased with increasing habitat heterogeneity, with sexual thrips apparently only persisting in certain types of hostplant communities. Our results illustrate how genetic diversity‐based mechanisms can favor asexuality instead of sex when sexual lineages co‐occur with genetically variable asexual lineages.